Morphologic changes of retina cellular elements under long low intensity light exposure - S. V. Logvinov; Ye. Yu. Varakouta; A. V. Potapov; Ye. P. Mikhoulya; A. A. Zhdankina (Бюллетень сибирской медицины)
Structural changes of eye retina in 40 male white rats under the influence of light with intensity of 200 lk during 1, 7, 14 and 30 days were studied using electron microscopy method and morphometric analysis. Structural changes of all cell elements of retina were revealed which were particularly expressed in neurosensory cells and in radial gliocytes. Maximum number of neurosensory cells with destruction of nucleus was observed after 7 days of exposure and achieves its maximum (4,6 ± 0,3)% compared to controls (0,40 ± 0,02)%. Changes of radial glial cells have both regressive and progressively -proliferative character. Changes of neurons of retina internal layers have mainly reversible character.